INOVASI PEMBELAJARAN MELALUI PENINGKATAN MEDIA TEKNOLOGI - Wahidin Wahidin (STAI AL FALAH Banjarbaru, 2019)
Learning media helps students in constructing knowledge in various world educational institutions. The development of technology helps learning media become easier to use. Various instructional media technologies have also become a trend and even help to learn resources across regional, national and continental boundaries. The development of instructional media always intersects with the culture of global learning behavior. Global culture is always influenced by the strong culture of developed countries such as countries on the American continent such as the United States and Canada, countries on the European continent such as Britain and Germany, countries on the Asian continent such as Japan and China. The cultural friction experienced by users of learning media is characterized by the use of global learning resources. Literature sources, connections with lecturers, access to URL addresses, broadcasts are largely a product of global culture. Keywords: Learning Media, Technology.